Active longitudinal motion control research of waterjet-propelled trimaran in random waves using direct CFD approach integrated with auto-control algorithm - Zhang, Lei; Chen, Hengxuan; Wei, Yuanhui; Zhang, Yi; Shang, Yuchen; Zhang, Jianing (Ocean engineering, 2023)
The current numerical method for ship motion control primarily relies on mathematical ship models that require solving hydrodynamic derivatives. In this paper, a fully nonlinear viscous computational fluid dynamics (CFD) model integrated with motion control strategies on an appendage was proposed to directly investigate the longitudinal motion control problem in random waves. The longitudinal motion control model was established on a free-running waterjet-propelled trimaran CFD model by combining a speed controller on the propulsor and attitude motion controller on the stern flap appendage. Through direct CFD simulations in random waves, the motion control capability of the stern flap under different control strategies, including fixed, linear, and PID controllers, was evaluated. The results show that the PID controller is superior and achieves a mean trough reduction of the pitch and heave by 22.3% and 15.6%, respectively. Subsequently, the longitudinal motion control capability of the stern flap under different lengths, traveling speeds, and sea states was numerically researched. The results indicate that as the speed and sea state increase, the pitch control effects of the stern flap on the trimaran appear to be saturated and mainly affected by the limited motion control force and moment. Thus by using joint control with other appendages, better longitudinal motion stability could be achieved. The proposed model provides a direct evaluation method for controlling ship motion by appendages in waves and accounts for complex hull shapes, nonlinear environments, and real-time hydrodynamic feedback. •A direct CFD approach of longitudinal motion control is proposed by integrating the different control algorithms.•The free-running waterjet-propelled trimaran CFD model with the motion control appendage of stern flap is established.•The non-linearity of the complex ocean environment and the real-time feedback of the viscous hydrodynamics are considered.•The PID controller shows the comprehensive motion reduction advantage than the fixed and linear control algorithm.•Motion attitude and propulsor revolution under different control strategies and wave conditions are effectively reduced.